Study on the period of acceptability of cooked rice (Journal of the Bangladesh Agricultural University, 2010)
The study attempts to determine the period of acceptability of cooked rice (parboiled) of Pajam variety. Cooling studies on cooked rice showed the highest cooling rate in soaked water, and successively followed by refrigeration, under fan air and at room temperature (30±2°C). The moisture, protein, fat, ash and total carbohydrate contents (wb) were 9.68, 4.93, 0.36, 0.32 and 84.71 % respectively in raw rice; 12.37, 8.36, 0.40, 0.57 and 78.29 % respectively in parboiled rice and 65.99, 3.24, 0.15, 0.14 and 30.47 % respectively in cooked rice (parboiled). After 24 hours of storage moisture, protein, fat, ash and carbohydrate contents were 66.47%, 5.69%, 0.13%, 0.14% and 15.73% respectively in rice at room temperature; 69.12 %, 3.64 %, 0.13 %, 0.13 % and 26.98 % respectively in refrigerated rice and 64.38 %, 3.53 %, 0.15 %, 0.15% and 31.78 % respectively in frozen rice. The cooked rice stored at room temperature for 24 hours showed 4.2x104cfu/g, and the refrigerated and frozen rice showed no viable load while after another 24 hours of storage the refrigerated rice showed 6.9x105cfu/g and frozen rice showed no load. The sensory evaluation revealed the 'cooked rice' and 'refrigerated and reheated rice' were equally acceptable and ranked as 'like very much' in terms of colour, taste, texture and overall acceptability. To ensure the maximum hygienic quality and desirable taste the cooked rice (parboiled) might be kept for a maximum period of 20 hours at room temperature and 48 hours in a refrigerator and reheated by microwave oven for 1 minute before serving to the consumer. Keywords: Period; Acceptability; Cooked rice DOI: 10.3329/jbau.v6i2.4840 J. Bangladesh Agril. Univ. 6(2): 401-408, 2008